Climate change and food security nexus in Ethiopia: challenges to food sustainability—a systematic literature review - Mekonen Getachew Abebe; Zerihun Yohannes Amare (Frontiers in Sustainable Food Systems)
IntroductionClimate change is currently one of the three major challenges facing the global population. Developing countries like Ethiopia are disproportionately affected by the negative impacts of climate change. Food security is highly jeopardized by climate-induced shocks such as drought and flood. This review aims to critically examine the interlinkages between climate change and food security in Ethiopia, highlighting key challenges, impacts, and potential policy responses.MethodsThis study adopts a systematic review of peer-reviewed literature on climate change and food security in Ethiopia, employing a realistic review approach. Before commencing the systematic review, databases were thoroughly searched for existing systematic reviews and meta-analyses to prevent duplication.ResultA total of 11 peer-reviewed articles were identified to investigate the relationship between climate change and food security in Ethiopia, revealing that climate change is a major factor aggravating food insecurity. Agriculture, the primary source of livelihood for the majority of the population is highly susceptible to climate change. This vulnerability directly affects the four components of household food security. The review also highlighted persistent forecasts of reduced crop production, land degradation, volatile market prices, and deteriorating livelihoods due to climate change, all contributing to food insecurity. Generally, climate change in Ethiopia is a setback to food security and is linked to broader development issues. Identified adaptation mechanisms include practicing climate-smart agriculture, implementing irrigation, managing soil and water resources, providing short-season seeds, planting drought-tolerant crops, altering planting dates, diversifying livelihoods, improving farmers’ awareness, and increasing the participation of female-led households in income-generating activities. The review recommends that Ethiopia, as a developing country, adopt locally suitable climate change adaptation strategies to enhance food security.